A 1600-year record of eolian activity from Jili Lake in northern Xinjiang. (10th September 2022) - Qiang, Mingrui; Lang, Wenzhe; He, Zhenhao; Jin, Ming; Zhou, Aifeng; Zhang, Jiawu
Abstract: Eolian activity determines the magnitude of dust emission. However, geological records of eolian activity are scarce due to strong wind erosion in the dust source areas. Northern Xinjiang is recognized as a major dust source region in arid central Asia. Here we present a lacustrine record of eolian activity over the past 1600 years from Jili Lake, in northern Xinjiang, which acts a natural trap for airborne materials. Based on the stratigraphic variability of two sedimentary sequences and 20 radiocarbon dates, we infer that Jili Lake initially developed in the southwestern part of the lake basin during the mid-Holocene and then expanded to close to its modern surface area until 1600 years ago. Grain-size analyses of materials from different parts of the lake sedimentary system, including lake surface sediments, lake catchment deposits, and airborne sand and dust collected from near the lakeshore, demonstrate that the coarse silt and fine sand fraction (40–200 μm) of the lake sediments was transported primarily by strong winds and can be regarded as an indicator of changes in eolian activity. We argue that wind strength played an important role in lifting and transporting the coarse particles, although an arid climate cannot be entirely excluded out as a factor favoring eolian activity. The most intensive eolian activity occurred from ∼910 to 1300 AD, roughly corresponding to the Medieval Warm Period (MWP), whereas eolian activity was weak during the Little Ice Age (LIA, ∼1300 to 1760 AD). However, this pattern is inconsistent with other dust records from central Asia. Eolian dust activity reflects the coupling of dust-generating windstorms and dust source areas which were swept by cold air surges. The spatial differentiation of eolian dust activity in arid central Asia may thus be causally linked to the intensity and extent of the Siberian High (SH), given that intense cyclogenesis always occurs on the southwestern periphery of the SH in springtime. Changes in the SH can be further ascribed to atmospheric circulation modulated by phase alternations of the North Atlantic Oscillation (NAO) due to large-scale thermal contrasts. Our results suggest that the dynamics of Asian dust emission are closely linked with the spatial variability of the SH. Nonetheless, more records of eolian activity are needed to further elucidate the forcing mechanisms of dust entrainment in the source area of Asian dust.